2016
DOI: 10.1111/ggi.12939
|View full text |Cite
|
Sign up to set email alerts
|

Social participation, willingness and quality of life: A population‐based study among older adults in rural areas of China

Abstract: Engagement in social activities is relatively low in rural areas, and associations of willingness and health-related quality of life with social participation were found. Policy-makers and government workers should make appropriate types of encouragement policies around social participation for older adults in rural areas. Geriatr Gerontol Int 2017; 17: 1593-1602.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 31 publications
(67 reference statements)
4
53
1
Order By: Relevance
“…This study outlined significant differences in the patterns of SP between urban and rural areas: compared with urban respondents, rural respondents were much less likely to take part in social activities, and the gap was especially significant in mah-jong or cards clubs, sports or social clubs and Internet use. This finding is in line with prior studies (Guo et al, 2018;He et al, 2017;Meng & Chen, 2014;Vogelsang, 2016).…”
Section: Patterns Of Social Participation In Urban and Rural Areassupporting
confidence: 93%
See 2 more Smart Citations
“…This study outlined significant differences in the patterns of SP between urban and rural areas: compared with urban respondents, rural respondents were much less likely to take part in social activities, and the gap was especially significant in mah-jong or cards clubs, sports or social clubs and Internet use. This finding is in line with prior studies (Guo et al, 2018;He et al, 2017;Meng & Chen, 2014;Vogelsang, 2016).…”
Section: Patterns Of Social Participation In Urban and Rural Areassupporting
confidence: 93%
“…Internet infrastructure, but the poorer community infrastructure failed to provide sufficient encouragement and opportunities for rural residents to widely participate in social activities (Bowling & Stafford, 2007;He et al, 2017).…”
Section: Patterns Of Social Participation In Urban and Rural Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [13,26] showed that rural older people were less socially active than urban older people. However, previous studies state that bonding social capital comprising a connection between community members is often stronger among rural older adults, resulting in community strength [27,28]. In addition, environmental factors such as neighborhood socioeconomic status and access to services and transportation differ in rural and urban areas [29].…”
Section: Introductionmentioning
confidence: 97%
“…In regard to demand factors, He et al (2017) indicated that the elderly demand covered economic security, health care maintenance, living care, psychological and social adaptation, education, leisure and social participation, and elderly protection. Cmar, McDonnall, & Crudden (2018) mentioned that those with worse health condition and serious limited functions used more diverse variety of welfare service, with higher use rate.…”
Section: Introductionmentioning
confidence: 99%